Investigation on hamburg wheel-tracking device stripping performance properties of recycled hot-mix asphalt mixtures - Rafiq, W. (MDPI AG, 2020)
Moisture damage in hot mix asphalt pavements is a periodic but persistent problem nowadays, even though laboratory testing is performed to identify different moisture-susceptible mixtures. In this study, a Hamburg Wheel Tracking device (HWTD) was used for rutting tests which were conducted on control and a high percentage of recycled asphalt pavement (RAP), i.e., 30, 50 and 100 of virgin mixtures, under air dry and water-immersed conditions. Similarly, the extracted bitumen from RAP was tested for binder physical properties. Results showed that the asphalt mixtures containing RAP have less rut depth as compared to the control mix both in air dry and immersion conditions and hence showed better anti-rutting properties and moisture stability. Stripping performance of control and RAP containing mixtures was also checked, concluding that the RAP mixture was greatly dependent on the interaction between the binder (virgin plus aged) and aggregates. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.